Covert visual spatial orienting and saccades: overlapping neural systems. - Nobre, A; Gitelman, DR; Dias, E; Mesulam, M (2000)
We used functional magnetic resonance imaging (fMRI) to investigate the functional anatomical relationship between covert orienting of visual spatial attention and execution of saccadic eye movements. Brain areas engaged by shifting spatial attention covertly and by moving the eyes repetitively toward visual targets were compared and contrasted directly within the same subjects. The two tasks activated highly overlapping neural systems and showed that common parietal and frontal regions are more activated during the covert task than the overt oculomotor condition. The possible nature of the relationship between these two operations is discussed.